Cannabis use preferences in women with myofascial pelvic pain: A cross-sectional study - Emily C. Yang; Nicole A. Koenig; Merry Gong; Lori A. Brotto; Alasdair M. Barr; Terry Lee; Paul J. Yong; Roxana Geoffrion (Elsevier, 2023)
Objective: Myofascial tenderness is present in most chronic pelvic pain conditions and causes significant distress to patients. Treatment is challenging and often not curative. Cannabis is often used for self-management of chronic pelvic pain. However, we do not know which concentrations and routes of administration are most acceptable to users. We aimed to investigate patterns and willingness of cannabis product use among both habitual users and non-users with myofascial pelvic pain (MPP), to inform therapeutic development. Study design: We conducted a cross-sectional study of questionnaire responses from female patients with MPP from two tertiary pelvic pain centers. We aimed for a convenience sample of 100 responses with representation from both centers. Inclusion criteria were age over 18 with pelvic floor muscle tenderness on standard gynecologic examination. We collected information on demographics, pelvic pain history, cannabis use status, cannabis use preferences, validated opioid misuse risk assessment, and interest in using gynecologic cannabis products and used descriptive analyses. Results: 77/135 (57 %) questionnaire respondents were cannabis users and 58 (43 %) were non-users. Most users consume cannabis daily, (48.1 %) orally (66.2 %) or by smoking (60.7 %), and rated cannabis as effective at relieving pelvic pain. 37/58 (63.8 %) non-cannabis users responded that they would be willing to use cannabis for pelvic pain. Lack of information and potential adverse effects were the most common reasons for unwillingness to use. Approximately 3 of 4 respondents were willing to try vaginal or vulvar application of cannabis products for pelvic pain. Conclusions: This cross-sectional study describes cannabis use patterns in MPP patients. Topical vulvar and vaginal cannabis products are of strong interest to both cannabis users and non-users and warrant further research.